Tetrabenazine in treatment of hyperkinetic movement disorders: an observational study. (February 2017) - Miguel, Rita; Mendonça, Marcelo D.; Barbosa, Raquel; Ladeira, Filipa; Lampreia, Tânia; Vale, José; Bugalho, Paulo
Background: Tetrabenazine (TBZ) is commonly used in hyperkinetic movement disorders. In this retrospective study, we aimed to assess the TBZ effectiveness and adverse events (AEs) in Huntington disease (HD), vascular chorea, tics, dystonia, tardive oromandibular (OM) dyskinesia and other tardive syndromes (TS). Methods: Qualitative analysis of clinical response was used to estimate TBZ effectiveness. TBZ-associated AE frequency and subsequent discontinuation rate were used to estimate tolerability; the tolerability profile was measured through the TBZ minimal dose and exposure time required to elicit AEs. Results: Of 108 included patients, 87% had a clinically meaningful improvement sustained over a period of 40 months. TBZ-responder rate ranged from 100% in HD to 62.5% and 77.1% in tic disorders and OM dyskinesia, respectively ( p < 0.001). TBZ-associated AE frequency ranged from 40.9% in other TS and 41.7% in vascular chorea and HD, to 60% in OM dyskinesia ( p < 0.001). The most common AEs were Parkinsonism (51.8%) and psychiatric disorders (25%). The 'other AEs' category (mainly somnolence) presented the shortest minimal exposure time (3 months). AE-eliciting dose differed from 18.8 mg and 25 mg in tics and tardive disorders, to 75 mg in HD ( p = 0.003). Patients with AEs were tendentiously older at TBZ initiation ( p = 0.022). Conclusions: TBZ proved an effective and relatively well tolerated treatment in hyperkinetic disorders, with excellent results in HD. AEs were more common in OM dyskinesia, which may be related to higher age at TBZ initiation. TBZ-associated somnolence and Parkinsonism were more frequent during the titration and maintenance periods, respectively.